Synthesis of Full-Length cDNA Infectious Clones of Soybean Mosaic Virus and Functional Identification of a Key Amino Acid in the Silencing Suppressor Hc-Pro - Wenhua Bao; Ting Yan; Xiaoyi Deng; Hada Wuriyanghan (Viruses, 2020)
Soybean mosaic virus (SMV), which belongs to the Potyviridae, causes significant reductions in soybean yield and seed quality. In this study, both tag-free and reporter gene green fluorescent protein (GFP)-containing infectious clones for the SMV N1 strain were constructed by Gibson assembly and with the yeast homologous recombination system, respectively. Both infectious clones are suitable for agroinfiltration on the model host N. benthamiana and show strong infectivity for the natural host soybean and several other legume species. Both infectious clones were seed transmitted and caused typical virus symptoms on seeds and progeny plants. We used the SMV-GFP infectious clone to further investigate the role of key amino acids in the silencing suppressor helper component-proteinase (Hc-Pro). Among twelve amino acid substitution mutants, the co-expression of mutant 2—with an Asparagine→Leucine substitution at position 182 of the FRNK (Phe-Arg-Asn-Lys) motif—attenuated viral symptoms and alleviated the host growth retardation caused by SMV. Moreover, the Hc-Prom2 mutant showed stronger oligomerization than wild-type Hc-Pro. Taken together, the SMV infectious clones will be useful for studies of host–SMV interactions and functional gene characterization in soybeans and related legume species, especially in terms of seed transmission properties. Furthermore, the SMV-GFP infectious clone will also facilitate functional studies of both virus and host genes in an N. benthamiana transient expression system.